Stereotactic radiosurgery and radiotherapy for resected brain metastases: current pattern of care in the Radiosurgery and Stereotactic Radiotherapy Working Group of the German Association for Radiation Oncology (DEGRO) : short communication - Rogers, Susanne; Baumert, B.; Blanck, O.; Böhmer, D.; Boström, J.; Engenhart-Cabillic, R.; Ermis, E.; Exner, S.; Guckenberger, M.; Habermehl, D.; Hemmatazad, H.; Henke, G.; et al. (Strahlentherapie und Onkologie, 2022)
Preoperative stereotactic radiosurgery (SRS) of brain metastases may achieve similar local control and better leptomeningeal control rates than postoperative fractionated stereotactic radiotherapy (FSRT) in patients treated with elective metastasectomy. To plan a multicentre trial of preoperative SRS compared with postoperative FSRT, a survey of experts was conducted to determine current practice.
Gesehen am 22.08.2023